Elastic, Mechanical, and Phonon Behavior of Orpiment Arsenic Trisulfide under Pressure. (19th September 2020) - Jiang, Liwu; Wu, Meiling; Shi, Peng; Zhang, Chuanhui
Abstract : Arsenic trisulfide (As2 S3 ) has been found to be an excellent glass former at high temperature and pressure. However, there is still some scarcity for the elastic and phonon behavior of the orpiment phase. By using the Dreiding force field of the geometry optimization computations, we investigated the elastic constants, mechanical moduli, and the phonon dispersion of orpiment As2 S3 under the pressure from 0 to 5 GPa. Some results of the elastic parameters of orpiment-As2 S3 at 0 GPa are consistent with the experimental data. The phonon dispersions for orpiment As2 S3 under pressure are also reasonable with previous calculations.